Reflection of violence, threats and aggression in a political space : a case of the post-apartheid novel Sehlekehleke Sa Deidro by V. Masima - Moeketsi, Victor (Southern African Journal for Folklore Studies, 2017)
The article is set to examine violence, threats and aggression in a political space, using TV Masina’s novel, Sehlekehleke sa Deidro (“An Island of Deidro”). The author of this article attempts to demonstrate how elements of folktales are incorporated into the works of modern writers. The article also aims to show how a character is in need of a living space, and how he/she responds to it according to socio-cultural norms; prescribed by the space. The theoretical aspects of violence, threats and aggression are discussed, followed by the definition of political space. Theory of space dominates the discussions, as it underpins the violent, threatening and aggressive behaviour of characters in the development of the novel. The findings reveal that the outer space (dangerous), as opposed to the inner space (safe), shows how characters depict the present state of affairs in the Southern African region today; where human life could be exterminated within a wink of an eye. The article argues in conclusion that corruption and mal-administration of resources by political leaders in the Southern African countries have corroded the moral fibre of communities, where evil has become the norm.
Published Article
Keywords: interdiction; folktales; politics; space; violation; violence